ZnAl-Humic Acid Composite as Adsorbent of Cadmium(II) From Aqueous Solution - Jeri Rahmadan; Veronika Parhusip; Neza Rahayu Palapa; Tarmizi Taher; Risfidian Mohadi; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
The modified ZnAl composites with humic acid (HA/ZnAl composite) were a coprecipitation method used as an adsorbent to remove cadmium(II) in an aqueous solution. The synthesized material was characterized using SEM-EDX, FTIR, and XRD. From the analysis using XRD, there is a widening peak at an angle of 2???? (24°), FTIR analysis there is a new peak at 1000 cm−1 and 1220 cm−1 and SEM analysis show that there is a change in surface morphology due to more aggregated particles. The experimental results on HA/ZnAl composite followed the PSO model, where the cadmium(II) removal process was chemical adsorption. The adsorption isotherm follows the Langmuir model where adsorption occurs in a monolayer and maximum adsorption capacity was obtained 38.76 mg/g higher than pristine. Thermodynamics of the adsorption process of cadmium(II) in an aqueous solution occurred spontaneously where G < 0 at all temperatures and endothermic properties were tested. The performance of the HA/ZnAl composite showed that strong potential as an adsorbent of low cost, high efficiency, easy operation, and good reusability. The cadmium(II) was absorbed on the surface of HA/ZnAl composite by surface complexation and chelating interactions, and surface complexation was the main route of cadmium(II) removal. In addition, HA/ZnAl composite has excellent treatment efficiency in actual aqueous solution.